1986
DOI: 10.1172/jci112656
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 16,600-dalton outer membrane protein on nontypeable Haemophilus influenzae as a target for human serum bactericidal antibody.

Abstract: A 16,600-D outer membrane protein is present in all strains of Haemophilus influenzae and antibodies to this protein are present in human serum. This study was designed to assess the role of this outer membrane protein (P6) in nontypeable H. influenzae as a target for human serum bactericidal antibody. P6 was isolated and coupled to an affinity column. Depleting normal human serum of antibodies to P6 by affinity chromatography resulted in reduced bactericidal activity of that serum for nontypeable H. influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 32 publications
2
94
0
Order By: Relevance
“…At the 30-min time point, there was consistently more killing in the normal human serum control than in the anti-loop 6 reaction mixture. Interestingly, these kinetics are similar to results with immunopurified antibodies to P6 used in bactericidal assays (19). No bactericidal activity was apparent in a control reaction mixture in which both complement and the anti-loop 6 antibody were omitted.…”
Section: Specificity Of Immunopurified Antibodies To Loopsupporting
confidence: 75%
“…At the 30-min time point, there was consistently more killing in the normal human serum control than in the anti-loop 6 reaction mixture. Interestingly, these kinetics are similar to results with immunopurified antibodies to P6 used in bactericidal assays (19). No bactericidal activity was apparent in a control reaction mixture in which both complement and the anti-loop 6 antibody were omitted.…”
Section: Specificity Of Immunopurified Antibodies To Loopsupporting
confidence: 75%
“…Since NTHI lacks capsular antigens, the chief antigenicity is present in the outer membrane proteins (OMPs). One of the OMPs of NTHI, P6, is a common antigen to all strains and is considered as a candidate for mucosal vaccine (7,9,10,11,30,31).In the mucosal surface, secretory immunoglobulin A (IgA) plays a major role in protective immunity. We previously demonstrated that intranasal immunization was an effective regimen for inducing mucosal IgA immune responses in the upper respiratory tract (26) and that the nasal mucosal IgA immune responses induced by intranasal immunization were effective for the clearance of bacteria in the nasopharynx.…”
mentioning
confidence: 99%
“…Since NTHI lacks capsular antigens, the chief antigenicity is present in the outer membrane proteins (OMPs). One of the OMPs of NTHI, P6, is a common antigen to all strains and is considered as a candidate for mucosal vaccine (7,9,10,11,30,31).…”
mentioning
confidence: 99%
“…The interstrain variation of P5 seen in NTHi (136) (10,115,143,145). It elicits bactericidal antibody in both its native (135,141) and recombinant (71) forms. Since this protein is highly conserved among encapsulated and nonencapsulated H. influenzae strains (140,148), surface exposed, and immunogenic (31,112,135), there has been much interest in it as a potential vaccine candidate.…”
Section: Outer Membrane Proteinsmentioning
confidence: 99%